Exploring the sustainability dimensions of coffee agro-industry: a critical review and future research agenda. Issue 1 (1st July 2022) - Hadi, A H; Suprihatin,; Pramuhadi, G
Abstract: The international coffee organisation is committed to providing information and conducting structured studies to regularly report on the development of relevant aspects or indicators of the coffee sector to reduce climate change and environmental impacts. The international community is progressively building green ecosystems that maintain an effective climate to create increased opportunities to promote low-carbon and climate-resilient development paths, and there are various kinds of drivers or indicators as key success factors in the custom and optional coffee agroindustry sector that must be considered following the social, environmental and system conditions that are implemented to achieve sustainable productivity. This paper aims to analyse the key dimensions of selected (literature) articles from 2010 to 2020 using Harzing's or Perish, Mendeley, Microsoft Excel and Vosviewer applications by identifying, extracting and synthesising several scientific articles related to agriculture. Coffee. Industry to be the basis of a sustainable future research agenda. The determination of the sustainable dimension refers to the need for future research (future research agenda) to be carried out, while the processing and critical review of the paper (a critical review) is carried out by classifying the key dimensions related to the total factor of green productivity. The results obtained on network overlay and density visualisation resulted in further research: (1) coffee consumption, (2) sustainable supply chain, (3) environmental sustainability, (4) green coffee beans, and (5) speciality or fine coffee.